First Documented Transmission of Trypanosoma cruzi Infection through Blood Transfusion in a Child with Sickle-Cell Disease in Belgium - Blumental, Sophie; Lambermont, Micheline; Heijmans, Catherine; Rodenbach, Marie-Pierre; El Kenz, Hanane; Sondag, Danièle; Bottieau, Emmanuel; Truyens, Carine (PLOS Neglected Tropical Diseases, 2015)
null